2016
DOI: 10.1097/jom.0000000000000679
|View full text |Cite
|
Sign up to set email alerts
|

The Big Five Personality Traits and French Firefighter Burnout

Abstract: Three of the Big Five personality traits, neuroticism, conscientiousness and openness to experience, and achievement goals, may be important factors in understanding and preventing firefighter burnout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 26 publications
1
12
0
1
Order By: Relevance
“…Firefighting is one of the highest risk professions in which repetitive exposure to traumatic experiences may lead to serious psychological consequences [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17]. Current studies indicate that the specific stress and workload of professional firefighters increases the risk of mental health symptoms [1], post-traumatic stress disorder [2,3], burnout [4,5,6,7,8], depression [9], and suicidality [10,11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firefighting is one of the highest risk professions in which repetitive exposure to traumatic experiences may lead to serious psychological consequences [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17]. Current studies indicate that the specific stress and workload of professional firefighters increases the risk of mental health symptoms [1], post-traumatic stress disorder [2,3], burnout [4,5,6,7,8], depression [9], and suicidality [10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Current studies indicate that the specific stress and workload of professional firefighters increases the risk of mental health symptoms [1], post-traumatic stress disorder [2,3], burnout [4,5,6,7,8], depression [9], and suicidality [10,11,12]. In this context, researchers accentuate the role of individual characteristics that may influence the potential consequences of experienced stress [10,13,14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Available literature on burnout in firefighters concludes that job demands and work control may be associated with burnout, and the age of a firefighter may be associated with emotional exhaustion [1]. Some time later a study in American firefighters showed that work-family conflict may also provoke burnout [2], whereas another study added that neuroticism out of five selected personality traits had a positive correlation with firefighters’ burnout [3]. Such weariness at work will not only decrease professional efficacy, but may be associated with elevated injury rates [4], and given high physical activity level in this population, may lead to significant absenteeism.…”
Section: Introductionmentioning
confidence: 99%
“…Grundy na podstawie badań do rozprawy doktorskiej ustaliła, iż neurotyczność wpływa na poziom wypalenia zawodowego w grupie 142 strażaków z USA. Zgodnie z uzyskanymi w pracy wynikami neurotyczność wyjaśnia 9% wariancji depersonalizacji, 21% wyczerpania emocjonalnego oraz 7% poczucia osiągnięć osobistych [19]. W opinii greckich badaczy V. Yotsidi i wsp.…”
Section: Dyskusjaunclassified